POTENSI DAYA TARIK OBYEK PARIWISATA DALAM PEMBANGUNAN EKONOMI SUMATERA BARAT (JURNAL ECONOMICA : Research of Economic And Economic Education, 2012)
The focus of this research is finding the contribution of economic for tourism activity in the west Sumatra province. Propose to development strategic economic for tourism destination West Sumatra area. The methodology approached for this research is positive economic approach with economic regional tools. Collected data carry out by mean of focus group discussion at the ten destination of tourism in west Sumatra province. The research result indicated that economic of contribution of tourism for economic structure West Sumatra very low. The Domination contribution of economic exhibited hotel and restoran indicator, journey and accommodation indicators are insignificant. West Sumatra of tourism destination have natural and culture attractive, beside environmental attractive, but it has not enough basic factor as toilets, sanitation, rest area, and basic infrastructure for tourism services.